Addendum to 2‐Butoxyethylacetate (Ethylene glycol monobutyl ether acetate) [BAT Value Documentation, 2016]. Issue 4 (19th October 2018) - Göen, T.; Rettenmeier, A.W.; Drexler, H.; Hartwig, A.; ,
Abstract: In 2015 the German Commission for the Investigation of Health Hazards of Chemical Compounds in the Work Area has re‐evaluated the biological tolerance value at the work place (BAT value) for 2‐butoxyethylacetate (ethylene glycol monobutyl ether acetate) [CAS No. 112‐07‐2 ], considering butoxyacetic acid in urine to characterise the internal exposure. Due to the high variability of conjugated amounts of the butoxyacetic acid and the limitation of conjugated amounts at high exposure levels the previous BAT value for free 2‐butoxyacetic acid is converted with a factor of 1.5. Additionally, the impact of diuresis is considered by the relation to the creatinine concentration. Therefore, a BAT value for the total butoxyacetic acid excretion of 150 mg butoxyacetic acid (after hydrolysis)/g creatinine was established. The sampling time is at the end of exposure/shift after several previous shifts. As the effects of the two glycol ethers 2‐butoxyethyl acetate and 2‐butoxyethanol are largely the same in the human organism, the BAT value applies to both and for combined exposure. The two substances were discussed together in the addendum of 2‐butoxyethanol.